Analyzing Training Outcomes: An In-depth Study on Understanding, Attitudes, Procedures, Output, and Food Security - Menaka C, Aishwary Awasthi, Vaibhav Srivastav (Revista Electronica de Veterinaria, 2024)
The dairy sector is vital to India’s financial system since it supports millions of producers and meets the country’s growing population’s nutritional demands. Problems with milk quality, however, severe obstacles that impact public well-being and competition in the market. This study investigates how customized training courses can address concerns with milk quality for dairy producers in India. The training for this study, which took place between 2014 and 2020, was made to be brief, easy to administer, affordable, and customizable. It also included incentives to encourage changes in understanding, attitude, and Procedures (UAP). The following results were evaluated in 2021: milk production, mastitis prevalence, and altered UAP. A few specific food safety risks were assessed as well, despite the fact that the administrators had to receive any training. While there were no changes in the severity of food safety hazards, we discovered indications of enhanced UAP among educated farmers, 13.8% more milk produced, and an orientation of reduced mastitis. The results of this study demonstrate the potential medium-term effects of training interventions, but food security is an intricate problem that isn’t likely to improve even with adequate instruction.